Impact of 5-Amino-1H Tetrazole on Reducing Silver in Copper Cathodes during Electrorefining with High Silver Content Anode Plates - Chen Chen; Chu Cheng; Mengxin Wang; Haitao Liu; Xiaoheng Li; Kexing Song (Metals, 2024)
As the grade of the copper concentrate decreases and its composition becomes increasingly complex, the silver content in anode plates cast after fire refining increases, leading to a higher silver content in the copper cathode during electrorefining and a substantial loss of precious metals. This study investigates the impact of 5-amino-1H tetrazole (5-AT) on reducing silver in copper cathodes during electrorefining with high silver content anode plates. 5-AT forms an “adsorption layer” on the anode surface, reacting with Ag+ released by the anode to form a precipitate and prevent Ag+ from entering the electrolyte. This process agglomerates fine Ag-Se compounds and AgCl particles, creating larger anode slime particles that settle quickly, thus inhibiting fine silver-containing particles from adhering to the cathode. Furthermore, 5-AT adsorbs on the cathode, binding with Cu+ and promoting the Cu2+ electrodeposition process while inhibiting Ag+ electrodeposition. This facilitates uniform copper cathode grain growth and reduces inclusions in the copper cathode. The grain size of the copper cathode initially decreases and then increases as the concentration of 5-AT increases. At an optimal 5-AT concentration of 15 mg/L, the Ag content in the copper cathode decreased from 6.9 ppm to 4.7 ppm, indicating the potential efficacy of 5-AT in improving the quality of electrorefined copper.